IMPLEMENTATION OF MENU ENGINEERING TO INCREASE COCKTAIL SALES AT GRAND MIRAGE RESORT & THALASSO BALI - I Gede Anggaditha Reksa Putra; Ida Ayu Elistyawati; Ni Made Ernawati (Politeknik Negeri Bali, 2018)
This study aims to find out about the menu of interest and less desirable by customers, also to know the menu has the highest and lowest contribution margin, and what strategies should be used to increase sales volume. The research method used is interview, observation and documentation. Data analysis technique used is menu engineering analysis technique. The analysis shows that in January there were 10 cocktails in category stars. 6 Drink Cocktails In category Puzzels. 10 Drink cocktails in the category of plowhorses and 4 drinks on category dogs. The cocktails that give high contribution margin are Long Beach, Mojito, Bloody Marry, Pinacolada, Tropical Moon, Abelito, Margarita, Mirage Punch Bella, Frostini, Cube Libre, Blue Lagoon, Caipirinha, Pluto Punch, Star Passion, Caipiroska. The cocktails that give the low contribution margin are Hurricane, Bali Comet, White Russian, Wet Bitch, Day Beach, Cosmopolitan. As expected, this study can be used to be a good advice and can be a good consideration by Grand Mirage Resort & Thalasso Bali in preparing the menu strategy and increasing the sales volume